A low-temperature preparation method of an alkali-resistant room-temperature phosphorescent carbon dot composite material in a confined state and application thereof

CN122878952APending Publication Date: 2026-10-09SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610996434.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]然而,上述制备方法普遍依赖数百摄氏度的高温煅烧过程,不仅能耗较高、制备工艺复杂,而且增加了材料制备成本,不利于制备

Benefits of technology

本发明一种限域型耐碱室温磷光碳点复合材料的制备方法采用溶胶–凝胶原位限域结合低温固化工艺,无需传统数百摄氏度高温煅烧即可完成碳点/二氧化硅复合材料的制备,整个过程条件温和、能耗低、操作简单,具有良好的绿色环保特性和规模化制备潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878952A_ABST
    Figure CN122878952A_ABST
Patent Text Reader

Abstract

The application discloses a low-temperature preparation method of a confined alkali-resistant room-temperature phosphorescent carbon dot composite material and application thereof, wherein a carbon dot precursor and a sodium silicate solution are mixed in an aqueous phase, a sol-gel reaction is triggered in situ by adjusting the pH of the system, a three-dimensional silicon dioxide network is constructed, uniform nano confinement of the carbon dots is realized, and a room-temperature phosphorescent composite material is obtained by low-temperature solidification at 60 DEG C. The process is green and environmentally friendly, and has low energy consumption; effective confinement of the carbon dots can be realized without high-temperature calcination; by virtue of the rigid confinement effect of the silicon dioxide network and the synergistic effect of the luminescent center on the surface of the carbon dots, the material is endowed with long-life room-temperature phosphorescent performance. The obtained composite material has excellent alkali-resistant stability, can still maintain stable afterglow emission in a strong alkali environment, and can be widely applied in the fields of anti-counterfeiting identification, information encryption and optical information storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of luminescent materials technology, specifically relating to a low-temperature preparation method and application of a confined alkali-resistant room-temperature phosphorescent carbon dot composite material. Background Technology

[0002] Room-temperature phosphorescence (RTP) materials, due to their long-lifetime luminescence and high signal-to-noise ratio, have broad application prospects in fields such as anti-counterfeiting, information encryption, biometrics, optical information storage, and bioimaging. In recent years, carbon dots (CDs) have become an important luminescent system for constructing RTP materials due to their advantages such as simple preparation, low cost, environmental friendliness, good biocompatibility, and tunable optical properties. However, the triplet excitons generated by carbon dots are easily deactivated non-radiatively by factors such as oxygen, moisture, and molecular thermal motion, severely limiting their RTP emission efficiency and duration. Therefore, effectively stabilizing the triplet excitons of carbon dots has become an important research direction in this field.

[0003] To improve the room-temperature phosphorescence performance of carbon dots, existing technologies typically employ a rigid matrix confinement strategy, encapsulating carbon dots within matrices such as silica, polymers, or inorganic salts. This restricts the vibration and rotation of the carbon dot luminescence centers, suppresses nonradiative relaxation, and enhances room-temperature phosphorescence performance. Silica, due to its excellent chemical stability, light transmittance, and ease of constructing three-dimensional network structures, is widely used in the preparation of carbon dot room-temperature phosphorescent composite materials. Existing technologies (such as CN118724003A and CN119081685A) disclose the preparation of carbon dot / silica room-temperature phosphorescent composite materials using a sol-gel combined with high-temperature calcination method. High temperatures promote further cross-linking and densification of the silica network, thereby achieving a longer-lifetime room-temperature phosphorescence emission.

[0004] However, the aforementioned preparation methods generally rely on high-temperature calcination processes at hundreds of degrees Celsius, which not only consumes a lot of energy and involves complex processes, but also increases the cost of material preparation, making them unfavorable for preparation. In addition, existing silica-based room-temperature phosphorescent materials are still prone to silica network framework collapse and hydrolysis in complex chemical environments such as strong alkalis, which weakens the protective effect on the carbon dot luminescent centers, resulting in a decline in phosphorescence performance and making it difficult to meet the requirements for long-term stable application in complex environments.

[0005] Therefore, developing a carbon dot / silica composite material that does not require high-temperature calcination, has a simple preparation process, and possesses excellent room-temperature phosphorescence properties and alkali resistance, along with its preparation method, is of great significance for promoting the application of room-temperature phosphorescent materials in fields such as anti-counterfeiting, information encryption, and information security. Summary of the Invention

[0006] The purpose of this invention is to provide a confined alkali-resistant room temperature phosphorescent carbon dot composite material, its preparation method and application. This method does not require high-temperature calcination. Through a sol-gel in-situ confinement strategy, a composite material in which carbon dots are uniformly confined in a three-dimensional cross-linked silica network can be obtained under low temperature conditions, so that the obtained material has both excellent room temperature phosphorescence properties and alkali resistance stability. To achieve the above objectives, the present invention employs the following technical solution: A low-temperature preparation method for a confined, alkali-resistant, room-temperature phosphorescent carbon dot composite material includes the following steps: Step 1: Disperse the carbon dot precursor in the inorganic silicon source solution and mix thoroughly to form a homogeneous mixture; Step 2: Add an acidic regulator to the mixture to induce a sol-gel reaction in the system, forming a three-dimensional silica wet gel in which carbon dots are confined. Step 3: Perform low-temperature curing treatment on the wet gel to obtain a confined alkali-resistant room temperature phosphorescent carbon dot composite material.

[0007] Furthermore, in step 1, the carbon dot precursor is prepared by a hydrothermal reaction of a carbon source, a nitrogen source, and an organosilane coupling agent.

[0008] Furthermore, the carbon source is glucose, the nitrogen source is urea, and the organosilane coupling agent is 3-aminopropyltriethoxysilane (APTES).

[0009] Furthermore, the carbon dot precursor is prepared by hydrothermal reaction of carbon source, nitrogen source and amino organosilane coupling agent at a ratio of 50 mg:300 mg:4 mL at 200 °C for 10 h. The specific process is as follows: glucose, urea and APTES are added to 10 mL of deionized water at a ratio of 50 mg:300 mg:4 mL, placed in a reaction vessel, and reacted at 200 °C for 10 h. After natural cooling, the carbon dot precursor solution is obtained by vacuum filtration and dialysis.

[0010] Furthermore, the volume ratio of the carbon dot precursor solution to the inorganic silicon source solution is (0.2~0.4) ml: 4 mL.

[0011] Furthermore, the inorganic silicon source is a sodium silicate solution.

[0012] Furthermore, in step 2, the acidity regulator is hydrochloric acid, and the pH of the system is adjusted to 6.8–7.2.

[0013] Furthermore, in step 2, after the wet gel is formed, the wet gel is washed alternately with deionized water and anhydrous ethanol to remove unreacted impurities and free carbon dots.

[0014] Furthermore, in step 3, the low-temperature curing treatment is performed at a temperature of 60–70 °C, preferably 60 °C, for a time of 10 h.

[0015] The present invention also provides a confined alkali-resistant room temperature phosphorescent carbon dot composite material obtained according to the preparation method, the composite material comprising a three-dimensional cross-linked silica network and carbon dots uniformly dispersed in the network.

[0016] Furthermore, under 364 nm excitation conditions, the average phosphorescence lifetime of the solid phase of the composite material is 1.23 s; under 361 nm excitation conditions, the average phosphorescence lifetime of the liquid phase of the composite material is 1.10 s.

[0017] Furthermore, the composite material retains room temperature phosphorescence even under strongly alkaline conditions of pH=13~14.

[0018] The present invention also provides an application of the aforementioned carbon dot confined alkali-resistant room temperature phosphorescent composite material in anti-counterfeiting identification, information encryption, optical information storage, QR code anti-counterfeiting, and latent fingerprint visualization.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a confined alkali-resistant room temperature phosphorescent carbon dot composite material. This method employs a sol-gel in-situ confinement combined with a low-temperature curing process, which eliminates the need for traditional high-temperature calcination at hundreds of degrees Celsius to prepare carbon dot / silica composite materials. The entire process is characterized by mild conditions, low energy consumption, and simple operation, exhibiting excellent green and environmentally friendly properties and potential for large-scale preparation.

[0020] This invention utilizes a three-dimensional cross-linked silica network to uniformly confine carbon dots in situ, effectively limiting the non-radiative energy loss of the carbon dot luminescence centers, resulting in a composite material with excellent room-temperature phosphorescence properties. Examples show that the obtained composite material achieves a solid-state absolute photoluminescence quantum yield of 29.2% and an average phosphorescence lifetime of 1.23 s.

[0021] The carbon dot / silica composite material constructed in this invention can maintain stable room-temperature phosphorescence emission under strongly alkaline conditions. After continuous ultrasonic treatment for 30 min in an alkaline environment with pH=14, the material still exhibits stable afterglow emission, indicating that the confined structure constructed in this invention has excellent chemical stability and alkali resistance, and can meet the requirements for long-term use in complex environments.

[0022] The composite material obtained by this invention has the advantages of low energy consumption preparation, excellent room temperature phosphorescence properties and alkali resistance, and can be widely used in anti-counterfeiting labels, information encryption, biometric identification and other fields, with broad application prospects. Attached Figure Description

[0023] Figure 1Transmission electron microscope image of the confined alkali-resistant room temperature phosphorescent carbon dot composite material prepared in Example 1 of this invention, with the inset being a high-resolution transmission electron microscope image; Figure 2 X-ray diffraction pattern of the composite material prepared in Example 1 of this invention; Figure 3 Fourier transform infrared spectrum of the composite material prepared in Example 1 of this invention; Figure 4 Afterglow emission pattern of the composite material prepared in Example 1 of this invention, excited by multiple excitation wavelengths; Figure 5 Solid-phase lifetime decay diagram of the composite material prepared in Example 1 of this invention under 364nm excitation; Figure 6 The liquid phase lifetime decay diagram of the composite material prepared in Example 1 of this invention under 361nm excitation; Figure 7 Comparison of time-resolved afterglow photographs of the composite material prepared in Example 1 of this invention after treatment in a strongly alkaline solution (pH=14); Figure 8 Photographs showing the actual anti-counterfeiting application effects of the composite material prepared in Example 1 of this invention in pattern encryption, QR code anti-counterfeiting printing, and latent fingerprint visualization. Detailed Implementation

[0024] The following detailed explanation of the specific content of the present invention is provided in conjunction with embodiments, but it is not intended to limit the present invention.

[0025] This invention discloses a low-temperature preparation method for a confined, alkali-resistant, room-temperature phosphorescent carbon dot composite material, comprising the following steps: Step 1: Disperse the carbon dot precursor in the inorganic silicon source solution at a volume ratio of (0.2~0.4) ml: 4 mL, and mix thoroughly to form a homogeneous mixture.

[0026] The inorganic silicon source is a sodium silicate solution.

[0027] The carbon dot precursor is prepared by hydrothermal reaction of a carbon source, a nitrogen source and an organosilane coupling agent. In this invention, the carbon source is glucose, the nitrogen source is urea, and the organosilane coupling agent is 3-aminopropyltriethoxysilane (APTES).

[0028] Specifically, glucose, urea, and APTES were added to 10 mL of deionized water at a ratio of 50 mg: 300 mg: 4 mL, placed in a reaction vessel, and reacted at 200 °C for 10 h. After natural cooling, the carbon dot precursor solution was obtained by vacuum filtration and dialysis.

[0029] Step 2: Add an acidic regulator to the mixture to induce a sol-gel reaction, forming a three-dimensional silica wet gel with carbon dots confined within it. The acidic regulator is hydrochloric acid, and the pH of the system is adjusted to 6.8–7.2.

[0030] After the wet gel is formed, it is washed alternately with deionized water and anhydrous ethanol to remove unreacted impurities and free carbon dots.

[0031] Step 3: Perform low-temperature curing treatment on the wet gel to obtain a confined alkali-resistant room-temperature phosphorescent carbon dot composite material.

[0032] During the low-temperature curing process, the temperature is 60–70 °C, preferably 60 °C, and the time is 10 h.

[0033] This invention also discloses a confined, alkali-resistant, room-temperature phosphorescent carbon dot composite material obtained according to the preparation method. The composite material comprises a three-dimensional cross-linked silica network and carbon dots uniformly dispersed in the network. Under 364 nm excitation conditions, the average phosphorescence lifetime of the solid phase of this composite material is 1.23 s; under 361 nm excitation conditions, the average phosphorescence lifetime of the liquid phase of this composite material is 1.10 s. This composite material retains room-temperature phosphorescence even under strongly alkaline conditions with pH = 13~14.

[0034] Example 1 Step 1: Weigh 50 mg of glucose, 300 mg of urea, and 4 mL of APTES, add them to 10 mL of deionized water, stir magnetically until completely dissolved, then transfer to a 100 mL polytetrafluoroethylene-lined high-pressure reactor and hydrothermally react at 200 °C for 10 h. After the reaction is complete, allow it to cool naturally to room temperature, vacuum filter the obtained product, and then dialyze it into a dialysis bag with a molecular weight cutoff of 1000 Da to obtain a carbon dot precursor solution. Step 2: Measure 0.4 mL of the carbon dot precursor solution and add it to 4 mL of saturated sodium silicate solution under magnetic stirring. Mix well and then slowly add dilute hydrochloric acid to adjust the pH of the system to 7.0, so that the system undergoes a sol-gel reaction to form a wet gel in which carbon dots are confined in a three-dimensional silica network. Step 3: The wet gel is washed alternately with deionized water and anhydrous ethanol to remove unreacted impurities and free carbon dots. The washed wet gel is then placed in a forced-air drying oven and cured at 60 °C for 10 h. After drying, the resulting solid is ground to obtain the confined alkali-resistant room-temperature phosphorescent carbon dot composite material.

[0035] The obtained composite material was characterized structurally, tested for phosphorescence properties, tested for alkali resistance, and validated in applications. The results are shown in the figures below. Figures 1 to 8 .

[0036] Example 2 The difference between this embodiment and Embodiment 1 is that in step 2, the amount of carbon dot precursor solution added is adjusted from 0.4 mL to 0.2 mL; and the resulting composite materials all exhibit room temperature phosphorescence properties.

[0037] Example 3 The difference between this embodiment and embodiment 1 is that in step 3, the low-temperature curing temperature is adjusted from 60 ℃ to 70 ℃; and the resulting composite material is observed to have room temperature phosphorescence properties.

[0038] The materials obtained in Examples 1-3 were tested and analyzed. (I) Structural Analysis of Composite Materials The composite material prepared in Example 1 was characterized by transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR).

[0039] TEM results as follows Figure 1 As shown, carbon dots are uniformly dispersed in a silica matrix; high-resolution transmission electron microscopy results indicate that the carbon dots have lattice fringes of approximately 0.21 nm, corresponding to the (100) crystal plane of graphitic carbon. XRD results are shown below. Figure 2 As shown, a broadened diffraction peak appears at approximately 23°, indicating that the obtained silica matrix has an amorphous structure. The FTIR results are as follows: Figure 3 As shown, the composite material retains characteristic functional groups such as hydroxyl, amino, and Si–O–Si, indicating that carbon dots were successfully incorporated into the three-dimensional silica network.

[0040] (II) Analysis of Phosphorescence Properties of Composite Materials The composite material prepared in Example 1 was subjected to spectral and lifetime tests using a fluorescence spectrophotometer.

[0041] like Figure 4 As shown, the obtained composite material exhibits significant room-temperature phosphorescence emission at different excitation wavelengths. Further testing of its lifetime characteristics yielded the following results: Figure 5 and Figure 6 As shown, under 364 nm excitation conditions, the average phosphorescence lifetime of the solid phase of the composite material is 1.23 s; under 361 nm excitation conditions, its average phosphorescence lifetime in the liquid phase is 1.10 s, indicating that the obtained composite material has a long room temperature phosphorescence lifetime and good liquid phase stability.

[0042] (III) Analysis of Alkali Resistance of Composite Materials The composite material prepared in Example 1 was added to a sodium hydroxide solution with pH=14 and treated continuously under ultrasonic conditions for 30 min.

[0043] After processing, time-resolved afterglow observation was performed on the sample, and the results are as follows: Figure 7 As shown, after ultrasonic treatment with a strong alkali, the composite material still retains blue room temperature phosphorescence, indicating that the obtained composite material has good alkali resistance and can meet the requirements for use in complex environments.

[0044] This invention also discloses the application of a carbon dot-confined alkali-resistant room temperature phosphorescent composite material in anti-counterfeiting identification, information encryption, optical information storage, QR code anti-counterfeiting, and latent fingerprint visualization, as detailed below: Composite material application verification The composite material prepared in Example 1 was used for pattern printing, QR code printing, and latent fingerprint visualization, respectively.

[0045] The results are as follows Figure 8 As shown, the resulting pattern can produce obvious light emission under ultraviolet light irradiation and maintain a continuous afterglow after the irradiation stops, which can be used for information encryption and pattern anti-counterfeiting. The prepared QR code can be normally recognized by the device in dry, humid and aqueous environments. At the same time, the material can clearly display latent fingerprints, indicating that the obtained composite material has good anti-counterfeiting application performance.

[0046] In summary, the low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material of this invention employs a green and environmentally friendly process with low energy consumption. It achieves effective confinement of carbon dots without high-temperature calcination, utilizing the rigid confinement effect of the silica network and the synergistic effect of the luminescent centers on the carbon dot surface to endow the material with long-life room-temperature phosphorescence properties. The resulting composite material exhibits excellent alkali resistance and stability, maintaining stable afterglow emission even in strongly alkaline environments, and can be widely used in fields such as anti-counterfeiting labels, information encryption, and optical information storage.

[0047] The above description is merely a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention in any way. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can be modified and replaced in several simple ways, and these modifications and replacements are all within the scope of protection covered by the claims.

Claims

1. A low-temperature preparation method for a confined, alkali-resistant, room-temperature phosphorescent carbon dot composite material, characterized in that, Includes the following steps: Step 1: Add the carbon dot precursor to the water-soluble inorganic silicon source solution and mix thoroughly to form a homogeneous mixture; Step 2: Add an acidic regulator to the mixture to allow the system to undergo a sol-gel reaction, forming a wet gel in which carbon dots are confined within a three-dimensional silica network; Step 3: The wet gel is subjected to low-temperature curing treatment to obtain a carbon dot confined alkali-resistant room temperature phosphorescent composite material.

2. The low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material according to claim 1, characterized in that, In step 1, the carbon dot precursor is prepared by hydrothermal reaction of a carbon source, a nitrogen source, and an amino organosilane coupling agent.

3. The low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material according to claim 2, characterized in that, The carbon source is glucose; the nitrogen source is urea; the aminoorganosilane coupling agent is 3-aminopropyltriethoxysilane; the carbon dot precursor is prepared by hydrothermal reaction of carbon source, nitrogen source and aminoorganosilane coupling agent at a ratio of 50 mg:300 mg:4 mL at 200 °C for 10 h.

4. The low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material according to claim 1, characterized in that, In step 1, the water-soluble inorganic silicon source is a sodium silicate solution; the volume ratio of the carbon dot precursor solution to the sodium silicate solution is (0.2-0.4) ml: 4 mL.

5. The low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material according to claim 1, characterized in that, In step 2, the acid regulator is hydrochloric acid, which is added until the pH of the system is adjusted to 6.8-7.

2.

6. The low-temperature preparation method of the confined alkali-resistant room-temperature phosphorescent carbon dot composite material according to claim 1, characterized in that, In step 3, the low-temperature curing treatment is performed at a temperature of 60–70 °C for 10 hours.

7. A confined, alkali-resistant, room-temperature phosphorescent carbon dot composite material obtained by the preparation method according to any one of claims 1 to 6, characterized in that, The composite material comprises a three-dimensional cross-linked silica network and carbon dots uniformly dispersed in the network.

8. The confined alkali-resistant room temperature phosphorescent carbon dot composite material according to claim 7, characterized in that, Under 364 nm excitation, the average phosphorescence lifetime of the composite material in the solid phase is 1.23 s; under 361 nm excitation, the average phosphorescence lifetime of the composite material in the liquid phase is 1.10 s.

9. The confined alkali-resistant room temperature phosphorescent carbon dot composite material according to claim 7, characterized in that, The composite material retains room temperature phosphorescence even under strongly alkaline conditions with pH=13~14.

10. The application of a carbon dot confined alkali-resistant room temperature phosphorescent composite material as described in any one of claims 7 to 9 in anti-counterfeiting identification, information encryption, optical information storage, QR code anti-counterfeiting and latent fingerprint visualization.

Citation Information

Patent Citations

  • Monodisperse long-life room-temperature phosphorescent carbon dot-silica microsphere and preparation method thereof

    CN118724003A

  • Preparation method of long-life room-temperature phosphorescent carbon dot and silicon dioxide composite material

    CN119081685A